2019
DOI: 10.1159/000503870
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 4 Study of Everolimus to Evaluate Efficacy and Safety in Patients with Metastatic Renal-Cell Carcinoma after Failure of First-Line Sunitinib or Pazopanib (SUNPAZ)

Abstract: Introduction: Sunitinib and pazopanib are both standard first-line therapies for clear-cell metastatic renal-cell carcinoma (mRCC). Everolimus is a well-established second-line treatment. Objective: To estimate the efficacy and safety of second-line everolimus following pazopanib or sunitinib. Methods: SUNPAZ was an open-label, phase 4 clinical trial of everolimus in patients with clear-cell mRCC progressing after first-line sunitinib or pazopanib. The primary end point was the number of patients without progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although there was no direct comparison between those two groups, the authors did not report any difference in overall survival regarding prior TKIs. Notably, the SUNPAZ (A Phase 4 Study of Everolimus to Evaluate Efficacy and Safety in Patients with Metastatic Renal-Cell Carcinoma after Failure of First-Line Sunitinib or Pazopanib) study had an appropriate study design for evaluating the influence of sunitinib and pazopanib on subsequent treatment [14]. The SUNPAZ trial is a phase 4, multicenter, prospective study that aimed to evaluate the efficacy and safety of everolimus in patients who progressed on prior anti-angiogenic treatments (sunitinib or pazopanib) in mRCC [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no direct comparison between those two groups, the authors did not report any difference in overall survival regarding prior TKIs. Notably, the SUNPAZ (A Phase 4 Study of Everolimus to Evaluate Efficacy and Safety in Patients with Metastatic Renal-Cell Carcinoma after Failure of First-Line Sunitinib or Pazopanib) study had an appropriate study design for evaluating the influence of sunitinib and pazopanib on subsequent treatment [14]. The SUNPAZ trial is a phase 4, multicenter, prospective study that aimed to evaluate the efficacy and safety of everolimus in patients who progressed on prior anti-angiogenic treatments (sunitinib or pazopanib) in mRCC [14].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the SUNPAZ (A Phase 4 Study of Everolimus to Evaluate Efficacy and Safety in Patients with Metastatic Renal-Cell Carcinoma after Failure of First-Line Sunitinib or Pazopanib) study had an appropriate study design for evaluating the influence of sunitinib and pazopanib on subsequent treatment [14]. The SUNPAZ trial is a phase 4, multicenter, prospective study that aimed to evaluate the efficacy and safety of everolimus in patients who progressed on prior anti-angiogenic treatments (sunitinib or pazopanib) in mRCC [14]. According to the result of this study, the median progression-free survival for patients in the sunitinib group was 2.8 months, whereas it was eight months in the pazopanib group.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this, large trials in pretreated adults with metastatic ccRCC had shown modest benefit in PFS with everolimus alone, 83,84 with a phase 4 trial also demonstrating improved OS 84 …”
Section: Treatmentsmentioning
confidence: 99%
“…First-line treatment modalities of metastatic renal-cell carcinoma (mRCC) have changed substantially during the last decade due to the introduction of new therapy regimens, mainly based on immune checkpoint inhibition (IO) [1][2][3]. Currently, four different types of approved first-line combination therapies are available for the treatment of intermediate and poor-risk mRCC according to the International Metastatic Renal-Cell Carcinoma Database Consortium (IMDC) score: (i) combination of αPD-1 and αCTLA-4 immune checkpoint inhibitors as well as (ii) combination of αPD-1 (or αPD-L1) with smallmolecule tyrosine kinase inhibitors (TKIs) targeting the vascular endothelial growth factor receptor [4][5][6][7][8][9]. In essence, these regimens can be classified as an intensified IO (IO + IO) and a combination of IO plus antiangiogenic therapy (IO + TKI).…”
Section: Introductionmentioning
confidence: 99%